Análisis de los gastos deducibles para fines de impuesto a la renta en el sector camaronero. - Mendoza Angamarca, Heidy Lisseth (My University, 2019)
The present work is based on making a reflection about the Deductible Expenses for the calculation of the Income Tax, the same one that in ancient times lacked, however for today this tax has been considered by the government mandatory and important for all the natural persons, undivided estates and companies, national or foreign, domiciled or not in the country according to their economic activity. The research carried out is aimed at determining the analysis of Deductible Expenses for Income Tax purposes in the shrimp sector. During the study process, a rational-deductive epistemological approach was used, in addition to the methodological approach to qualitative and quantitative research. In addition, practical exercises are proposed with expenses of Provisions for Eviction and Employer Retirement, Losses in Non-current Assets, Taxes and Contributions, Travel Expenses, Management and Promotion Costs and Advertising, demonstrating the deductibility of said expenses. Finally, it is concluded that the application of accounting and tax regulations is essential in the business sector that through Servicio de Rentas Internas (SRI) as a responsible entity fosters the tax culture in the citizenry and in this way contribute to the country in a positive manner in the distribution of resources and improvement of society.
El presente trabajo se basa en realizar una reflexión acerca de los Gastos Deducibles para el cálculo de Impuesto a la Renta, el mismo que en tiempos antiguos carecía, en cambio, para la actualidad este gravamen ha sido considerado por el gobierno obligatorio e importante para todas las personas naturales, las sucesiones indivisas y las sociedades, nacionales o extranjeras, domiciliadas o no en el país conforme a su actividad económica. La investigación realizada está orientada a determinar el análisis de los Gastos Deducibles para fines de Impuesto a la Renta en el Sector Camaronero. Durante el proceso del estudio se usó un enfoque epistemológico racional- deductivo sumado al enfoque metodológico alusivo a la investigación cualitativa y cuantitativa. Además se plantea ejercicios prácticos de gastos de Provisiones por Desahucio y Jubilación Patronal, Pérdidas en Activos No Corrientes, Tributos y Aportaciones, Gasto de Viaje, Gastos de Gestión y Promoción y Publicidad demostrando la deducibilidad de dichos gastos. Finalmente se concluye que la aplicación de la normativa contable y tributaria es indispensable en el sector empresarial que por medio del Servicios Rentas Internas (SRI) como ente responsable fomente la cultura tributaria en la ciudadanía y de este modo aportar al país de manera positiva en la distribución de recursos y mejora de la sociedad.
Keywords: GASTOS DEDUCIBLES; CONTRIBUYENTE; LEY; RECAUDACIÓN